Impact of reduction degree on stability of Fe2O3-MgAl2O4 oxygen storage materials during chemical looping reverse water-gas shift reaction - Van Cauwelaert, Michiel W.F.; Buelens, Lukas C.; Singh, Varun; Poelman, Hilde; Detavernier, Christophe; Padevět, Jaroslav; Schwarzová, Hedvika; Galvita, Vladimir V.; Van Geem, Kevin M. (Journal of CO2 utilization, 2024)
This study investigates the long-term stability and performance in chemical looping reverse water-gas shift reaction (rWGS) of a 50 wt% Fe2O3-MgAl2O4 material produced using an industrial method. While prior research predominantly focuses on short-term deactivation of lab-scale materials, this research explores the complex relationship between the cycle duration, material performance and stability of an upscaled material. Through comprehensive analyses, successful upscaling is demonstrated. Performance tests on the upscaled material reveal that shorter cycle durations lead to superior CO space-time yield, with a steady-state deactivation rate of 0.07 %/h over 28 days on stream. During the first 225 h of redox time, the equilibrium CO2 conversion for catalytic rWGS is exceeded. Characterization post-cycling identifies key deactivation mechanisms, underscoring the challenge of maintaining stability over extended cycles. Rietveld refinement and STEM-EDX mapping indicate the formation of FexMg1-xAl2O4 and MgFe2O4 phases, the former of which contributes to reduced redox capacity, as indicated by temperature-programmed reduction measurements before and after cycles. Optimal performance was observed with shorter cycles despite lower material utilization, emphasizing the trade-offs between performance and stability. This research provides comprehensive insights for optimizing chemical looping CO2 utilization processes, vital for advancing scalable and economically viable solutions to combat carbon emissions. •Long-term stability of Fe2O3-MgAl2O4 oxygen storage material over 28 days on stream.•Influence of cycle duration on material performance.•Equilibrium conversion of CO2 for catalytic rWGS exceeded during the first 225 h of redox time.•Steady-state deactivation rate of 0.07 %/h.•Structural evolution towards FexMg1-xAl2O4 and MgFe2O4 phases.